2022
DOI: 10.3390/cells11071113
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methylases and Demethylases Regulating Antagonistic Methyl Marks: Changes Occurring in Cancer

Abstract: Epigenetic regulation of gene expression is crucial to the determination of cell fate in development and differentiation, and the Polycomb (PcG) and Trithorax (TrxG) groups of proteins, acting antagonistically as complexes, play a major role in this regulation. Although originally identified in Drosophila, these complexes are conserved in evolution and the components are well defined in mammals. Each complex contains a protein with methylase activity (KMT), which can add methyl groups to a specific lysine in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 209 publications
2
15
0
Order By: Relevance
“…They showed that, although the protein is catalytically inactive, the mouse is viable and fertile, contrary to the KDM5B knockout mouse, which displays an embryonic lethal phenotype 43 . These data confirm several observations regarding the relevant biological effects of KDM5 demethylases that are not dependent on their catalytic activity 12,37,[44][45][46] . We hypothesized that the NTT protein could be recruited to genomic sites through the PHD domains and retain some noncatalytic regulatory functions of KDM5B and/or compete for the catalytic functions of the PLU-1 isoform.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They showed that, although the protein is catalytically inactive, the mouse is viable and fertile, contrary to the KDM5B knockout mouse, which displays an embryonic lethal phenotype 43 . These data confirm several observations regarding the relevant biological effects of KDM5 demethylases that are not dependent on their catalytic activity 12,37,[44][45][46] . We hypothesized that the NTT protein could be recruited to genomic sites through the PHD domains and retain some noncatalytic regulatory functions of KDM5B and/or compete for the catalytic functions of the PLU-1 isoform.…”
Section: Discussionsupporting
confidence: 90%
“…The deregulated expression of KDM5 enzymes has been extensively documented in many cancer types and contributes significantly to tumor initiation and progression 12 . Specifically, KDM5B is a master regulator of H3K4-methylome in stem cells, development, and cancer 13 .…”
Section: Introductionmentioning
confidence: 99%
“…That epitranscriptomics and general epigenetic molecular mechanisms can play an essential role in determining the cell fate in development and differentiation is becoming increasingly clear [ 11 ]. Joyce Taylor-Papadimitriou and Joy M. Burchell have clearly shown the changes occurring in cancer determined by histone methylases and demethylases [ 12 ]. These epigenetic regulators can suppress the oncosuppressor genes and activate the oncogenes, leading to cancer progression [ 12 ].…”
Section: Autoimmunity and Antitumor Responsementioning
confidence: 99%
“…Histone acetylation and methylation are two major epigenetic marks that are removed by erasers, including the zinc-dependent histone deacetylases (HDACs) and the FAD-dependent lysine-specific demethylase 1 (LSD1, also known as KDM1A) that are both targets for EPIDD [ 5 , 6 ]. While LSD1 has a single well validated substrate in histone H3 [ 7 ], the eleven human HDAC isozymes are highly diverse in their function [ 8 ].…”
Section: Introductionmentioning
confidence: 99%